Reducing Abdominal Fat Deposition in Broiler Through Feeding Management - Cecep Hidayat (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2015)
Abdominal fat in broiler carcass is considered as a waste and its existence reduces the carcass quality. Abdominal fat deposition is affected by several factors such as genetic, nutrition, feed, sex, age and environment. Reducing abdominal fat deposition can be carried out by regulating the nutrient intake to ensure that no excessive nutrient was consumed. Nutrition effects to reduce abdominal fat deposition are associated with nutrient concentration of ration and quantity of daily feed intake. Daily nutrient intake can be limited, especially through restricted feeding. It is concluded that an appropriate feeding management can reduce abdominal fat deposition in broiler. Key words: Broiler, abdominal fat, feed